Synergistic Action of Plants and Microorganism in Integrated Floating Bed on Eutrophic Brackish Water Purification in Coastal Estuary Areas - Liu, Ming; Chen, Youyuan; Wu, Yadong; Guo, Jiameng; Sun, Ping; Zhang, Zhiming (Frontiers in Marine Science, 2021)
Eutrophic water bodies in coastal estuary areas usually show saline-alkaline characteristics influenced by tides. The purification performance of traditional planted floating beds in this water body is limited because of the poor growth of plants. A novel integrated floating bed with plants (Iris pseudoacorus), fillers (volcanic rocks and zeolites), and microbes named PFM was established, and the pollutant removal performance was studied. Results showed that the average ammonia nitrogen (NH4+-N), total nitrogen (TN), total phosphorus (TP), and permanganate index (CODMn) removal efficiencies of PFM were higher with the value of 81.9, 78.5, 53.7, and 72.4%, respectively, when compared with the other floating beds containing plants (P), fillers (F), microbes (M), and plants and fillers (PF) in this study. Therein, the most of NH4+-N (30.1%), TN (27.9%), TP (22.5%), and CODMn (43.6%) were removed by microbes, higher than those removed by plants and fillers. Analysis of the microbial community revealed that the establishment of PFM led to a higher microbial richness than M, and Acinetobacter, as the main microbes with the function of salt tolerance and denitrification, were dominated in PFM with a relative abundance of 6.8%. It was inferred that the plants and fillers might enrich more salt-tolerance microbes for pollutants removal, and microbes favored the growth of plants via degradation of macromolecular substrates. Synergistic actions in the process of eutrophic brackish water purification were established. This study provided an idea for the application of integrated floating bed in eutrophic and brackish water bodies purification in coastal estuary areas.